Reconsidering Islamic Education Pedagogical Approach within Islamic Studies - Prasetia, Senata Adi (Jurnal Penelitian Pendidikan Islam, 2024)
This paper proposes a pedagogical approach to Islamic education in contemporary Islamic studies. During this time, Islamic Studies in Indonesia tended to be approached with an approach such as integrative-interconnective that connects with the surrounding material row, but less include the approach of Islamic education pedagogy in it. The indoctrination process carried out by scholars so far uses a teaching process that is inseparable from the science of education itself. This paper argues that the Islamic education pedagogical approach should start from the very vital component of education, i.e. teacher since the teacher contributes significantly to the development of students in almost all aspects. Also, pedagogical competence is important to have as a part excellence. This conceptual paper, therefore, proposes and develops a model of the approach of Islamic education pedagogy ranging from philosophical foundations to the practice of Islamic education pedagogy. In this paper, this kind of approach is intended to enable teachers to be agents of change as well as facilitators in providing enrichment of more varied, innovative, and creative perspectives.